Promoting awareness programmes for Malaysian women: Does practice matters? - Ahmad, Zalinah; Ahmad, Noor Azizah (2013)
Ministry of Women, Family and Community Development (MWFCD) has been responsible for incorporating women in development and enhancing the standard of living of women and family in Malaysia.In fact, the population of women in Malaysia is nearly half of the total population in year 2011.The Ministry has been responsible to design and implement programmes to create awareness among women about their rights, and issues relating to their concerns.The Ministry, together with women's NGO, has been helping each other to ensure that women will get the benefits from the programmes. However, with the recent changes in social media, have the Ministry and those NGOs been able to fulfill their responsibilities? Thus, this paper will explore and highlight the current practice of part of the Ministry and NGOs in creating awareness among women's issues in Malaysia.It will include the using of social media towards changes in women's community.Discussion will also include the opportunity and challenges faced regarding this partnership.